Technical considerations regarding saliva sample collection to achieve comparable protein identification and detection via one- and two-dimensional gel electrophoresis among humans - Szabolcs Maar; Lilla Czuni; Jørgen Kosberg Hassve; Aniko Takatsy; Szilard Rendeki; Tibor Mintal; Ferenc Gallyas, Jr.; Ildiko Bock-Marquette (Heliyon)
Background and aims: Recently, demands towards identifying various molecules in support of stress detection and potential clinical utilization are dramatically increasing. Moreover, the accuracy with which researchers quantify these informative molecules is now far more improved when compared to the past. As RNA or protein markers are conventionally detected via repeated invasive procedures from blood, it is critical to develop secure technologies to obtain the desired information via less stressful methodologies, such as saliva collection. Moreover, for superb interpretation, it became equally significant to obtain the information from the same exact specimen. RNA is easily degradable, thus it is paramount to supplement the samples with protective agents, such as RNAlater, to achieve accurate quantitative results. Methods: In our research we investigated whether and how this commonly applied RNA protection procedure influences protein and peptide separation of the human saliva via quantitative two-dimensional protein electrophoresis. Results: Our results revealed, in contrary to previously published data regarding plasma, the addition of RNAlater to saliva samples negatively influences isoelectric focusing and protein detection. We equally found the application oftentimes employed referred to as selective precipitation and reduction-alkylation, partially rescued separation, however, with a significant loss in protein yield and quality when compared to untreated samples. Conclusion: Our results suggest collection of human saliva for biomarker identification must be performed with extreme diligence. We propose application of RNAlater should be avoided and snap freezing of the collected saliva is recommended when joint protein and RNA quantification is the ultimate goal.